Rethinking local content requirements in EU public procurement within the paradigm of sustainable development - Kola, Jarosław (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
The European Union (EU) has traditionally opposed local content requirements (LCRs) in public procurement, viewing them as contrary to the principles of free trade and competition. However, recent global crises, including the COVID-19 pandemic, geopolitical tensions, and supply chain disruptions, have prompted a reconsideration of these policies. This article explores how the concept of sustainable development, enshrined in EU law, provides a framework for justifying LCRs under specific conditions. By analysing EU case law and policy developments, the study argues that LCRs can be permissible if they serve broader strategic goals determined within the sustainable development paradigm, such as environmental protection and social welfare, rather than economic protectionism. Ultimately, the findings suggest that carefully designed LCRs can enhance economic resilience while remaining compatible with EU legal principles. It is, however, crucial to emphasize that LCRs may be permissible, provided that they are proportionate to the contracting authority’s objectively justified needs, assessed with due diligence.